Dienogest in long-term treatment of endometriosis - Schindler AE (Dove Medical Press, 2011)
Adolf E SchindlerInstitute for Medical Research and Education, Essen, GermanyAbstract: Endometriosis is a chronic disease primarily affecting women of childbearing age, in which endometriotic lesions form outside the uterus, typically leading to painful symptoms, fatigue, and infertility. The symptoms of endometriosis may cause significant impairment in quality of life and represent a substantial economic burden to patients, families, and society. There is no cure for endometriosis; management consists of alleviating pain and other symptoms, reducing endometriotic lesions, and improving quality of life. Recurrence after surgical intervention is common, while the clinical evidence to support the efficacy and safety of many medications currently used in endometriosis is limited. Dienogest is an oral progestin that has been investigated extensively in the treatment of endometriosis in two clinical programs performed in Europe and Japan, including dose-ranging, placebo-controlled, active comparator-controlled, and long-term (up to 65 weeks) studies. These studies demonstrated that dienogest 2 mg daily effectively alleviates the painful symptoms of endometriosis, reduces endometriotic lesions, and improves indices of quality of life. Dienogest showed a favorable safety and tolerability profile in these studies, with predictable adverse effects, high rates of patient compliance, and low withdrawal rates. This review article describes the clinical trial evidence that characterizes the efficacy and safety of dienogest in endometriosis, including two studies characterizing dienogest in long-term use. The relevance of these findings to the management of endometriosis in clinical practice is discussed.Keywords: dienogest, endometriosis, progestins, long-term treatment, quality of life, symptoms, pain